The Immunopathology of Experimental Visceral Leishmaniasis - Kaye, Paul M.; Svensson, Mattias; Ato, Manabu; Zubairi, Soombul; Engwerda, Christian R. (Immunological reviews, 2004)
Experimental murine infection with the parasites that cause human visceral leishmaniasis (VL) results in the establishment of infection in the liver, spleen, and bone marrow. In most strains of mice, parasites are eventually cleared from the liver, and hepatic resistance to infection results from a coordinated host response involving a broad range of effector and regulatory pathways targeted within defined tissue structures called granulomas. In contrast, parasites persist in the spleen and bone marrow by mechanisms that are less well understood. Parasite persistence is accompanied by the failure of granuloma formation and by a variety of pathologic changes, including splenomegaly, disruption of lymphoid tissue microarchitecture, and enhanced hematopoietic activity. Here, we review the salient features of these distinct tissue responses and highlight the varied roles that cytokines of the tumor necrosis factor family play in immunity to this infection. In addition, we also discuss recent studies aimed at understanding how splenomegaly affects the survival and function of memory cells specific for heterologous antigens, an issue of considerable importance for our understanding of the disease-associated increase in secondary infections characteristic of human VL.